Analisis Penerapan Efisiensi Energi (Studi Kasus: Gedung III Fakultas Teknik dan Sains UPN “Veteran” Jawa Timur) - Farah Eka Putri Ramadaniati; Yayok Suryo Purnomo; Praditya Sigit Ardisty Sitogasa (Jurnal Serambi Engineering, 2025)
Energy use plays an important role in human survival and activities, but the issue of conventional (non-renewable) energy crisis is often a topic of discussion. Some scientists predict that this energy will run out in the near future. The amount of energy is increasing along with the growth in the number of infrastructure and buildings to support the development of the human population. Applying the green building concept to buildings is one way to achieve energy efficiency. This research aims to analyze and optimize the application of green building concept in terms of energy efficiency in Building III, Faculty of Engineering, UPN "Veteran" East Java. The analysis was carried out on aspects of lighting, air conditioning, energy savings modeling using EDGE 3.0.0 software, as well as calculating the intensity of energy consumption. Based on the analysis, the building known that has an energy consumption intensity value of 24.92 kWh/m²/month and has made energy savings through the use of energy-saving lighting and air conditioning, with savings of 18.09% compared to similar buildings.